Human Rights Violation In The Context Of Terrorist Groups' Crimes In Papua - Nurita, Riski Febria; Sunarjo; Rafid, Rahmad (Universitas Kristen Cipta Wacana, 2025)
Study This aiming For to study practice deletion right basic human rights (HAM) in Handling crime group terrorists in Papua, as well as to examine the extent to which state policies and actions are in line with principles law national and international . Research This use approach law normative with analysis to regulation legislation , doctrine law , and studies case human rights violations reported by institutions national and international . Findings show that determination group armed Papua as terrorist own impact Serious to protection of human rights, especially in form restrictions freedom express , action repressive apparatus , and limitations access to information and justice . In a number of case , action enforcement law tend beyond limit principle proportionality and legality . Although the state has right For guard stability and security , things the No can made into justification on neglect rights base citizens . Research This recommend strengthening approach humanistic , governance reform security , as well as improvement accountability enforcement law as an alternative strategy in finish conflict in Papua in general fair .